Papers - - Produciton - Domestic- Oil and Gas Development in Mississippi - B. C. Craft (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1935)
Development and exploratory work in Mississippi during 1934 was rather active, resulting in the expansion of the proven area and the drilling of a number of important wildcat wells. Mississippi showed a decrease in drilling operations during 1934. There were 36 completions from 18 counties during this period compared with 58 completions from 22 counties during 1933. There was a considerable decrease in activity in the Jackson gas field in Hinds and Rankin counties with only 9 completions, resulting in 8 gas wells and 1 dry hole compared with 17 gas wells, 2 oil wells and 7 dry holes during 1933. Leasing and geophysical work was reported from several sections of Mississippi last year. Extensive exploration and drilling were carried on in Lamar, Hancock, Pearl River, Greene and Stone counties and on the flanks of the Jackson anticline. Exploration will be continued in these areas during 1935. Four important wildcats were completed during 1934, all of which were reported as being structurally high, but without having important shows of oil or gas. These tests were: Hix and Germany's, J. J. Newman Lumber Co. No. 1, sec. 21-4N.-15W., Lamar County, abandoned at 3520 it. in the Wilcox; United Gas Public Service Company's Davis No. 1, sec. 30-1N.-5W., Greene County, abandoned at 7439 ft.; Gulf Refining Company's May L. Williams No. 1, sec. 33-5S.-17W., Pearl River County, abandoned at 4800 ft.; and Clarke County Oil Company's S. B. Kirkland No. 1, sec. 10-2 N.-16E., abandoned at 4002 ft. in the Eutaw. Another interesting wildcat was Gulf Refining Company's Dantzler Lumber Co. No. 6, sec. 22-4S.-llW., Stone County, abandoned at 7700 ft. (according to reports below the Selma chalk). A total of 114 of the 132 gas wells completed in the Jackson gas field are still producing and have a combined open-flow capacity of 4,145,-696,000 cu. ft. Four of the abandoned gas producers were never connected to the lines. The open-flow capacity of three wells in the Amory field is approximately 1,000,000 cu. ft. Producing against a line pressure of 50 lb., the demand during December greatly exceeded the capacity.